만성질환으로 입원한 환자의 의료추구행태에 관한 조사 연구 : 일 대학부속 병원을 중심으로 - 오정숙 (연세대학교 보건대학원, 1987)
[한글] 우리나라는 전통적의료기관과 현대적의료기관이 혼재되어 있기 때문에 사람들은 아프면 다양한 의료추구를 하고 있다. 따라서 이 연구는 만성질환으로 입원한 환자의 의료추구행태를 파악하여 건강사업계획을 위한 기초자료를 제공하고자 시도된 조사연구이다. 연구대상자는 연구자가 임의 선정한 서울Y대학부속병원에 입원한 만성질환자 150명을 임의로 선택하였다. 연구도구는 문헌과 고려대학교 지역사회 보건개발위원회서 개발한 도구를 기초로 작성한 21문항의 의료행태측정도구를 사용하였다. 자료수집기간은 1987년 4월 10일부터 4월 26일까지 총 17일간이었다. 자료분석을 위해 인구, 사회문화적특성은 실수와 백분율을 구하였고, 인구, 사회문화적특성과 의료추구행태, 대상자의 질병상태와 의료추구행태의 관련성은 χ**2 -test를 이용하여 분석하였다. 연구의 결과는 다음과 같다. 1. 만성질환자는 다양한 의료추구를 하고있는 것으로 나타났으며, 만성질환자들이 5차까지 이용한 의료기관 (의료유사기관)은 자가치료, 약국, 병원, 의원, 기도원, 한의원등 6가지 형태로 분류할 수 있었다. 즉 질병이환시 일관성있게 의료기관을 추구하지 못하고 현대의료기관과 전통의료기관을 번갈아가면서 이용하고 있었으며, 의료추구행태는 추구횟수가 증가할수록 병원 추구가 많은 것으로 나타났다. 2. 대상자를 암환자와 다른 만성질환자로 분류했을 때 1차추구에서만 암환자의 경우 입원을, 만성질환자의 경우 약국을 많이 찾는 것으로 나타나 차이를 보였을뿐 2차추구 이후에서는 두집단 모두 병원을 가장 많이 찾고 있었다. 3. 대상자가 현재 질병치료를 위해 종합병원에 입원해 있으면서도 다른 치료를 겸하는 경우가 23.2%이었으며 다른 치료의 내용으로는 민속 및 자가치료가 51.6%로 가장 많았고 한약도 병용하고 있었으며 자가치료 내용으로는 영지버섯과 고슴도치내장, 굼뱅이등을 치료를 보완하기 위해서 이용하고 있었다. 4. 대상자의 질병상태에서 질병이 있다는 것을 자신이 알아내는 계기는 증상이 있어서 자발적으로 진찰받고 아는 경우가 73.3%로 가장 많았고 처음 증상을 의식하였을때는 별로 지장이 없는 상태 42.0%로 가장 많았다. 치료처 선택에 대한 의사결정자를 3차추구까지 보았을 때 1차선택에서는 혼자 정하는 경우가 가장 높았으나 추구횟수가 늘수록 의료인이 많은 영향을 미치고 있는 것으로 나타났다. 대상자의 처음 진단에 대한 신뢰는 완전신뢰가 54.7%이었고 신뢰하지 않는 경우도 7.4%였다. 회복할 것이라는 기대는 완치를 기대하는 군이 76.2%였고 대상자의 첫번째 치료후 상태변화는 별변화가 없음이 31.5%이었으며 악화되는 경우도 9.6%였다. 5. 1차의료추구행태를 병의원형, 자가한의약국형으로 분류하여 인구, 사회문화적변수와의 관계를 χ**2 -test로 분석한 결과 인구, 사회문화적변수와 의료추구행태는 통계적으로 유의한 관계가 없는 것으로 나타났다. 6. 1차의료추구행태에 영향을 미치는 질병상태에 관한 요인으로는 처음 증상을 의식하였을 때의 상태, 치료처 선택에 대한 의사결정권, 첫번째 치료후 상태변화, 그리고 암이냐 다른 만성질환이냐 하는 진단분류에 대해서만 유의한 관계가 있는 것으로 나타났다. 이상의 결과로 볼 매 만성질환으로 입원한 환자의 의료추구행태는 병원선택이 가장 높았으나 일관성없이 다양한 의료추구를 하고 있는 것으로 나타나 올바른 의료추구행태를 위해선 질병발생 초기에 의료인이 적절한 교육과 상담을 제공해줄 필요가 있다. [영문] In Korea there are both traditional and modern medical care institutions, so that persons seeking medical care have various opportunities open to them. This study surveyed the medical care seeking behavior of patients hospitalized for chronic disease. The purpose was to discover where health professionals might intervene to guide patients with chronic disease to the most appropriate are, early in their medical care search. Participants in this study were 150 patients hospitalized for 11 different Chronic diseases in Y University Hospital in Seoul. Data were collected from April 10th to 26th, 1987 by interview using a schedule of 21 questions developed by the investiator from the literature. Demographic-sociocultural characteristics were analyzed by frequency and percentage. The relationships between medical care seeking behavior, the demographic sociocultural characteristics, and disease status were analyzed by chi-square. Results included the following: 1. Subjects displayed a wide variety of medical care seeking behaviors. They had used sox types of care facilities-traditional heal medicine, drug stores, general hospitals, private clinics, religious retreat centers and herb doctors. A typical patient used many facilities in rabid succession. The more facilities sought out the more often hospitals were used. 2. When patients were classified into two groups, cancer patient and others, cancer patients tended first to seek care at hospitals while other patients sought care at drug stores. Hospitals were often chosen by both groups for their second search. 3. During admission to this general hospital, 23.2% of the total group were receiving other treatments , particularly folk medicine (for example, certain fungi) (51.6%), and herb medicine (36.3%). 4. Patients generally recognized their own disease symptoms first (73.3%) but did not consider them serious enough to warrent seeking medical care (42.0%). The patients themselves tended to choose the first medical care facility. After that, behavior was influenced by the advice of professional medial workers. Many patients believed their first diagnosis to be correct (54.7%). Many expected a full recovery from the beginning (76.2%). Some patients thought they had made no progress after their first treatment (31.5%) and some felt their condition bad deteriorated (9.6%). 5. There were no significant differences in demographic or sociocultural characteristics between trio groups of patients when divided into those who firsts sought treatment at traditional care or at modern medical facilities. 6. Relationships between the first sought medical care and the disease status included the patient's condition when the symptoms first developed, the advice given by the first medical professional, the change in condition after the first care, and whether then was a diagnosis of cancer. Most subjects had sought care in a hospital prior to this hospitalization, although they had tried a wide variety of medical care facilities. They need sound advice from medical professionals early in their care seeking experience to choose the care best suited for their health problems.
보건학과/석사